IMMUNE STATUS OF BULL CALVES’ ORGANISM IN CASE OF EXPERIMENTAL CHRONIC CADMIUM TOXICOSIS - Lavryshyn, Y. Y.; Gutyj, B. V. (Scientific Progress & Innovations, 2020)
Cadmium intake is associated with environmental risk to the organism due to its cumulative toxicity to organs and systems. The accumulation of the above-mentioned heavy metal in the components of the natural environment increases the risk of its entry into the body and poses a threat to animal health. The aim of the study was to investigate the effect of cadmium on the immune status of young cattle, namely on the humoral and nonspecific parts of the immune system. The research was conducted on a farm in the village of Ivaniv-tsi, Zhydachiv district, Lviv region, on 10 bull calves of six months of age, Ukrainian black-spotted dairy breed, which were formed into 2 groups of 5 animals each: control and experimental. The bull calves of the control group were on a normal diet. The bull calves of the experimental group were fed with feed contain-ing cadmium chloride at a dose of 0.04 mg / kg of the animal body weight. Cadmium was found to suppress the nonspecific and humoral part of the immune system during 30-day load of young cattle. It was estab-lished that under cadmium loading, the phagocytic activity of neutrophils in the blood of bull calves of the experimental group beginning from the 15th day of the experiment decreased. It was also found that the low-est phagocytic index was on the 20th day of the experiment, when it decreased by 18.2 % as compared with the control group. Studying the humoral part of the bull calves’ immune system under cadmium loading, a probable decrease in bactericidal and lysozyme activity of the bull calves’ blood serum by 8.5 and 3.3 %, respectively was registered, relative to the control group of animals. After adding cadmium chloride to the feed of bull calves of the experimental group, the level of circulating complexes probably increased from the 10th day of the experiment. A high level of circulating immune complexes in the blood serum of bull calves indicates the suppression of the organism's immune system as a result of the attaching specific antibodies to the products of metabolism under cadmium load. On the 15th and 20th days of the experiment, the level of circulating immune complexes in the blood of animals of the experimental group increased by 9.7 and 13.4 %, respectively. The obtained data will be used in the further study of the cellular part of the immune system of bull calves and for the development of an antidote preparation for the treatment of animals with cadmium toxicosis.